BEST study: one-year descriptive follow-up of bevacizumab treatment in hereditary haemorrhagic telangiectasia post-BABH interventional study - Sophie Dupuis-Girod; Evelyne Decullier; Sophie Rivière; Christian Lavigne; Vincent Grobost; Vanessa Leguy-Seguin; Hélène Maillard; Thierry Chinet; Anne-Emmanuelle Fargeton; Alexandre Guilhem; Ruben Hermann (Therapeutic Advances in Hematology)
Background: Hereditary haemorrhagic telangiectasia (HHT) is a genetic vascular disorder characterised by telangiectases, which cause nasal and gastrointestinal (GI) bleeding, and visceral arteriovenous malformations. Since 2012 bevacizumab, a monoclonal antibody targeting vascular endothelial growth factor, has been a promising treatment for HHT-related bleeding and was evaluated in the phase II BABH study. Objective: To follow and describe evolution and treatments of patients with HHT post-BABH study. Design: This study is a 1-year, multi-centre descriptive study. Methods: We collected clinical (nose and GI bleeding, red blood cell transfusions) and biological (haemoglobin and ferritin levels) data and treatment information. Results: Of 22 patients included across 4 centers, 15 received bevacizumab. Among them, 12 (86%) had a >50% decrease in the number of RBC units transfused 3 months post-treatment. Mean haemoglobin levels increased from 83.08 to 105.98 g/L. Conclusion: Bevacizumab effectively reduces RBC transfusions and is efficient for treating severe bleeding in patients with HHT. Trial registration: This trial was registered with the ClinicalTrials.gov Identifier #NCT06039124.